What to do when hiccups are coming? A case report - Salim, Sonia E.; Suryana, Ketut (International Journal of Advances in Medicine, 2023)
Hiccup known as innocuous symptom and usually self-limiting within seconds or minutes. The process of hiccup related to involuntary movement, intermitent and repetitive contractions of diaphragm and lead to abrupt early closure of glottis. We report a case of 57-year-old man with 5 days chronic hiccup, following with coughing, nausea, vomiting and seizure. Patient was hospitalized 4 days and getting better after given antibiotic, proton pump inhibitor (PPI) therapy and symptomatic drug due to hiccup.